Knowledge, attitudes and practices of public health midwives on adolescent and youth friendly health services and their role in Gampaha District, Sri Lanka - P. V. S. C. Vithana; B. M. N. D. Batugedara; R. I. W. Nilaweera; A. C. M. Basnayake; C. J. Jayasundera; H. M. I. Handagiripathira; A. N. J. Barnasuriya (College of Community Physicians of Sri Lanka, 2022)
Introduction: Public health midwife (PHM) is the grass-root level health care provider for adolescents.   Objectives: To assess PHMs' knowledge, attitude, and practices on their role in provision of adolescent and youth friendly health services (AYFHS) in Gampaha District   Methods: A descriptive cross-sectional study was conducted in Gampaha District in 2019 using self-administered questionnaire. Scores for knowledge, attitudes and practices were expressed with median and interquartile range. Selected variables were presented using frequency distributions. Chi-Squared test or Fishers' exact test was used to assess associated factors with knowledge, attitude, and practice levels.   Results: Of 483 eligible persons, 90% (n=433) responded. Median age was 42 years (IQR: 36-51). A majority (n=339; 78.5%) accepted that "PHM has a role to play in AYFHS". Percentages identifying the PHMS' role in registering adolescents, identifying risky adolescents during home visits, providing details of AYFHS clinic, referring needy adolescents to it, and following risky adolescents in the field were 94% (n=406), 93.8% (n=405), 76.9% (n=332), 73.6% (n=318), 76.9% (n=332) and 76.6% (n=331), respectively. A positive attitude regarding their contribution on prevention of adolescent health issues, providing AYFHS services in the field were reflected among 300 (n=86.2%) and 351 (97.3%) respectively. Median percentage scores with IQR on knowledge, attitude and practices were 71.4 (52.5-98.9), 40 (25-55) and 47.6 (35.6-61.9). PHMs with satisfactory level of knowledge, attitudes and practices over 75% regarding their role in providing AYFHS were 46.7%, 12% and 9.7%. Satisfactory level of knowledge was positively associated with receiving training on adolescent health with in last three years (p=0.02) while age of 40 years and below was significantly associated with satisfactory level of attitude on PHMs' role in AYFHS (p=0.02).   Conclusions & Recommendations: PHMs' perception of their role in AYFHS was unsatisfactory. Implementation of targeted interventions for changing attitudes and practices on AYFHS is recommended.